Acting on incidental findings in research imaging. (10th November 2015) - Wardlaw, J M; Davies, H; Booth, T C; Laurie, G; Compston, A; Freeman, C; Leach, M O; Waldman, A D; Lomas, D J; Kessler, K; Crabbe, F; Jackson, A
Abstract : Incidental findings of imaging research studies can turn healthy individuals into anxious patients, while putting an extra burden on primary care. J M Wardlaw and colleagues argue that doctors should ensure that the personal, ethical, healthcare, and cost implications of these common findings are managed proportionately, sensitively, and economically